THE DEVELOPMENT OF MATHEMATICAL MODEL OF ECONOMIC EFFICIENCY OF PRODUCTION OF THIN-FILM STRUCTURES - Elena Olegovna Tarasenko; Andrey Vladimirovich Gladkov; Vasily Sergeyevich Tarasenko; Alexey Vyacheslavovich Shaposhnikov (Современная наука и инновации, 2022)
Article is devoted to mathematical modeling of economic efficiency of process of growth of thin-film structures which is poorly studied both theoretically, and practically now. Process of production of such structures is rather labor-consuming and demands considerable investments. The main production objective is planning of level of intensity of production so that the total revenue of the enterprise was maximum. Creation of mathematical production model is based on use of tools and methods of optimization. The objective comes down to the solution of a problem of linear programming. Mathematical modeling of production of thin-film structures has considerable practical and theoretical value in the modern scientific world.